All‐Oxide Transparent Thin‐Film Transistors Based on Amorphous Zinc Tin Oxide Fabricated at Room Temperature: Approaching the Thermodynamic Limit of the Subthreshold Swing. (11th September 2020) - Lahr, Oliver; Bar, Michael S.; von Wenckstern, Holger; Grundmann, Marius
Abstract: Thin‐film transistors (TFTs) based on transparent amorphous oxide semiconductors (TAOSs) have become essential building blocks for a broad range of electronics, since TAOSs facilitate large‐scale fabrication at moderate temperatures and hence feature compatibility with flexible substrates. An emerging indium‐free alternative to the widely commercially exploited indium gallium zinc oxide (IGZO) is amorphous zinc tin oxide (ZTO); however, according to previous reports, achieving acceptable performance of ZTO‐based devices fabricated at temperatures below 300 °C is still challenging to date. Here, key properties of the first all‐oxide and fully transparent metal‐semiconductor field‐effect transistors (MESFETs), metal‐insulator‐semiconductor field‐effect transistors (MISFETs) and junction field‐effect transistors (JFETs) based on amorphous ZTO are compared, employing PtO x, HfO y, and p ‐type NiO as gate, respectively. All individual layers have been deposited exclusively at room temperature and do not require any additional postdeposition annealing to obtain sufficient device functionality. Demonstrated TFTs exhibit reasonable current on/off ratios of over six orders of magnitude with subthreshold swings as low as 61 mV dec –1 at room temperature. Transistor characteristics have been recorded for several weeks to study performance consistency over time and are further investigated regarding their stability under bias stress. Abstract : All‐oxide and fully transparent metal‐semiconductor‐, metal‐insulator‐semiconductor‐, and junction field‐effect transistors based on amorphous zinc tin oxide are compared. Demonstrated transistors exhibit current on/off ratios higher than six orders of magnitude and subthreshold swings as low as 61 mVdec –1, while fabricated at room temperature without being exposed to any postdeposition annealing treatment.